Advances in Chromodomain Helicase DNA-Binding (CHD) Proteins Regulating Stem Cell Differentiation and Human Diseases - Liu, Caojie; Kang, Ning; Guo, Yuchen; Gong, Ping (Frontiers in Cell and Developmental Biology, 2021)
Background: Regulation of gene expression is critical for stem cell differentiation, tissue development and human health maintenance. Recently, epigenetic modifications of histone and chromatin remodeling have been verified as key controllers of gene expression and human diseases. Objective: In this study, we review the role of chromodomain helicase DNA-binding (CHD) proteins in stem cell differentiation, cell fate decision and several known human developmental disorders and cancers. Conclusion: CHD proteins play a crucial role in stem cell differentiation and human diseases.